Inculcating soft skills in UMP Engineering students through `RAKSI’ program - Haslinda, Hashim; Muhamad Zahim, Sujod (2008)
Technical skill is one of the most important elements needed amongst students especially Engineering students. Nevertheless, Soft Skills should not be ignored and lately, it has been given a great attention. Students with good grades will usually excel even better if they have high Soft Skills. Soft Skills also known as Kemahiran Insaniah (KI) is one of the listed skills needed by the industries in job advertisement or during job interview. With this fact, Universiti Malaysia Pahang has taken the initiative to introduce UHS1011 (Soft Skills 1) in students’ program curriculum and this subject is valued as one credit hour since academic session 2004/2005. UHS1011 (Soft Skills 1) is carried out throughout 14 weeks with 14 modules where students will be evaluated based on their participation in a program called RAKSI (Rakan Siswa). RAKSI is handled by competent facilitators which are selected among UMP academic associates (lecturers and tutors). The modules were developed by UMP Felo Institute where all activities have a continuity to implement communication skills, leadership skills and teamworking skills. Most activities will use psychomotor, cognitive and emotional approaches. Students will communicate with each other, solve problems given to them, interact while listening to instructions given by a leader in the activity. This paper hopes to expose how RAKSI has helped to implement Soft Skills elements through a structured program and also evaluate the effectiveness of the module to the students